KARAKTERISTIK SOSIAL EKONOMI MASYARAKAT PESISIR PANTAI KECAMATAN KEMA KABUPATEN MINAHASA UTARA (Social Economic Characteristics Coastal Community in Kema District North Minahasa Regency) - Jebrindah Lolowang; Lyndon R. J. Pangemanan; Melsje Y. Memah (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
This study aims to describe the socio-economic characteristics of coastal communities in Kema District, North Minahasa Regency. The data collected in this study were primaryÂ and secondary data. Sampling was done by purposive sampling as many as 50 samples. The majority of the coastal community were fishermen. Most of them only have elementary and junior high school education (78%). The condition of clean water and the environment was good. The community's economy was quite good with the status of owning a house as much as 64% and the average monthly incomes was above Rp. 3,000,000.